2012
DOI: 10.3109/14767058.2011.638952
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum interleukin-6 and its association with clinicopathological infectious morbidity in preterm premature rupture of membranes: a prospective cohort study

Abstract: Maternal serum IL-6 can be used as a biomarker to predict preclinical asymptomatic infection in PPROM with good sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
3
30
0
1
Order By: Relevance
“…This is truly important in under-developing countries in which there is no access to invasive procedures for an accurate diagnosis of HCA, such amniocentesis or vaginal amniotic fluid analysis. In 1997, Shimoya et al [29] found maternal serum concentrations of IL-8 as a screening marker for HCA, while similarly to our study, most authors agree that women with PPROM have higher serum levels of IL-6 [9,13,16,18,19,29].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This is truly important in under-developing countries in which there is no access to invasive procedures for an accurate diagnosis of HCA, such amniocentesis or vaginal amniotic fluid analysis. In 1997, Shimoya et al [29] found maternal serum concentrations of IL-8 as a screening marker for HCA, while similarly to our study, most authors agree that women with PPROM have higher serum levels of IL-6 [9,13,16,18,19,29].…”
Section: Discussionsupporting
confidence: 49%
“…In cases of intrauterine infection, cytokines produced within the uterine cavity first mount a local inflammatory response, and then reach the maternal circulation and the liver to stimulate the synthesis of C-reactive protein (CRP) by hepatocytes or bone marrow targets to induce leukocytosis [11][12][13]. Therefore, a rise in cytokines occurs earlier than CRP [14].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Other markers of inflammation detectable in the amniotic fluid or fetal membranes have previously been examined in the setting of suspected intrauterine infection; however, to date they have not had adequate utility to translate into regular clinical practice. 8,13,14 Sampling these tissues requires invasive procedures likely to be accepted by a limited number of women concerned about the potential harm from such procedures. 15,16 We undertook a prospective study where we set out to identify an mRNA-based biomarker in maternal blood that can identify the presence of chorioamnionitis in utero, among women who had PPROM.…”
Section: Discussionmentioning
confidence: 99%
“…uPAR enfeksiyondan korunmada önemli bir moleküldür. Özellikle lökosit adhezyon ve migrasyonunu tetikleyerek immün defans› güçlendirir (17) . Savva ve arkadafllar› sepsisli hastalarda yapt›klar› ça›lflmada sepsis tan›s› ve ciddiyetinin tahmininde yüksek serum uPAR düzeyleri ile iliflkili oldu¤unu göstermifllerdir (18) .…”
Section: G‹r‹fiunclassified